The Therapy with Oral Anticoagulants in Patients with Atrial Fibrillation in Outpatient and Hospital Settings (Data from RECVASA Registries) - M. M. Loukianov; S. Yu. Martsevich; O. M. Drapkina; S. S. Yakushin; A. N. Vorobyev; K. G. Pereverzeva; A. V. Zagrebelnyy; V. Val. Yakusevich; V. Vl. Yakusevich; E. M. Pozdnyakova; T. A. Gomova; E. E. Fedotova; et al. (Столичная издательская компания, 2019)
Aim. To evaluate an incidence of oral anticoagulants (OAC) administration during longterm follow-up period in patients with atrial fibrillation (AF) enrolled in outpatient and hospital RECVASA registries.Material and methods. 3169 patients with AF were enrolled in outpatient registries RECVASA (Ryazan), RECVASA AF-Yaroslavl and hospital registries RECVASA AF (Moscow, Kursk, Tula), age 70.9±10.7 years, 43.1% men. The incidence of OAC administration was evaluated in hospital and outpatient settings, including longterm follow-up period (2-6 years).Results. OAC were administrated only in 42.2% of cases (1335 from 3169 patients; age 69.1±10.4 years, 43% men), including warfarin (817 patients; 26%) and non-vitamin K antagonist oral anticoagulants (NOAC) - 518 (16%). Patients with permanent and persistant types of AF had lower incidence of OAC administration (43% and 40%) than in cases of paroxysmal type (47.6%, p<0.05), despite of the higher СНА2DS2-VASc risk score (4.69±1.66 and 4.23±1.57 vs 3.81±1.69; р<0.05). Patients with and without history of stroke received OAC in 42.5% and 40% of cases that means no significant difference (p>0.05) contrary to the pronounced difference of thromboembolic risk in these groups (6.14±1.34 and 3.77±1.39; р<0.001). The incidence of OAC administration in hospitals (54.1%) was 2.3 times higher than before hospitalization (23.8%) and was 4.1 times higher than in outpatient registries (13.5%). During follow-up period after hospital treatment (2.3±0.9 years) this parameter decreased from 54.1% to 41.2%, but was still 1.8 times higher than before admission to the hospital. After 4 years follow-up in RECVASA (Ryazan) registry we revealed 4.4 times higher incidence of OAC administration compared with enrollment data (4.2% and 18.3%, р<0.0001). This data was confirmed by the information from outpatient medical cards of accidentally generated group (75 from 297 patients survived during follow-up period): 5.3% at baseline and 22.7% six years later.Conclusions. RECVASA registries in 5 regions of Russia revealed low incidence of OAC administration. The risk of thromboembolic events was higher in patients with AF and no OAC administration compared with patients who received OAC. Patients with paroxysmal type of AF received OAC more often than those with permanent type. There were no significant differences of incidence of OAC therapy in patients with and without history of stroke. Both questioning of patients with AF and analysis of medical cards in outpatient clinics revealed higher incidence of OAC administration after 4-6 years of follow-up compared with the stage of enrollment in registries.